Innovation-Based Local Food Management Training: Pelatihan Pengelolaan Pangan Lokal Berbasis Inovasi - Cenny Putnarubun; Inay Kristina Maranressy; Betty N. Ohoirat; Thomas E. T. Rahayaan; Ricardo Freedom Nanuru (Yayasan Ahmar Cendekia Indonesia, 2022)
Local food management based on innovation made from ((Manihot esculenta Crantz) enbal and seaweed carried out as community service (PKM) by the STIA Darul Rachman Tual Research and Community Service Institute (LP2M). The purpose of PKM is to improve the ability to manage casava toxi or enbal (local name ) and seaweed as local food that has innovative value located in Ohoitel Village, North Dullah Island District, Tual City and growing lung business after pandemi covid-19. The method used is an innovation-based local food management training made from ((Manihot esculenta Crantz) (enbal) and seaweed as local food for the Kei Islands. The results obtained are in the form of innovative products as foods that have high culinary value and are nutritious and healthy without preservatives, namely seaweed chips, casava toxi or enbal chookies and seaweed noodles. The hope from this training is that food products have advantages and competitiveness and create new businesses in the field of local food based on innovation as an added value economically. Abstrak Pengelolaan pangan lokal berbasis inovasi berbahan enbal ((Manihot esculenta Crantz) dan rumput laut yang dilaksanakan sebagai pengabdian kepada masyarakat (PKM) oleh Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIA Darul Rachman Tual. Tujuan PKM adalah meningkatkan kemampuan penggelolaan enbal dan rumput laut sebagai pangan local yang memilki nilai inovatif yang berlokasi didesa Ohoitel Kecamatan Pulau Dullah Utara Kota Tual dan menumbuhkan usaha baru pasca pandemic covid-19. Metode yang digunakan adalah Pelatihan penggelolaan pangan local berbasis inovasi berbahan dasar enbal dan rumput laut sebagai pangan local kepulauan Kei. Hasil yang diperoleh berupa produk inovasi sebagai makanan yang memilki nilai usaha kuliner yang tinggi dan bergizi serta sehat tanpa pengawet yakni chips lumput laut, chookies enbal ((Manihot esculenta Crantz) dan mie rumput laut. Harapan dari pelatihan ini produk pangan yang memiliki keunggulan dan daya saing serta menciptakan usaha-usaha baru dalam bidang pangan local berbasis inovasi sebagai nilai tambah secara ekonomis.